A novel metric of measuring performance for supply chain risk management drawbacks and qualities of good performance - Shahbaz, Muhammad Saeed; Rasi, R.Z.R.; Zulfakar, M. H.; Ahmad, M. F.; Abbas, Z.; Mubarak, M. F. (University of El Oued, 2018)
The aim of this study is to consider the purposes, weakness and qualities of good performance measures and also to briefly explain various approaches and frameworks for supply chain performance for risk management and propose a new metric that measures overall performance for supply chain risk management. This is a conceptual paper, a content analysis approach have been operationalized for the literature review. This study concludes that a good metric for measuring performance for supply chain risk must contain seven indicators that are cost, quality, flexibility, customer satisfaction, capacity, time and consistency. This study will help managers to understand what they should consider, while developing key performance indicators. In addition, for future study empirical and theoretical support is required